RETRACTED: A novel cotton cleaning section design with innovative branched gears - Мamatova Dilrabo; Turgunov Muhammad Ali; Tyurin Igor; Nabiyev Abdumutal (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001